Hemolytic disease of the newborn due to combination of anti-E and anti-S in the first pregnancy - Kanra, Tekin; Tunçer, Müyesser; Pırnar, Aysel (The Turkish Journal of Pediatrics, 1983)
Hemolytic disease in a newborn infant, the product of a first pregnancy, is reported. A combination of anti-E and anti-S is shown as the cause of the disease. In view of the absence of a previous antigenic stimulus, the antibodies present are most probably naturally occurring IgG antibodies.
Keywords: antibody identification; anti-E; anti-S; blood group antibodies; hemolytic disease of the newborn; naturally occurring antibody